The social-demographic characteristics and pandemic COVID-19 individual experience and their impact on vaccination attitude study aimed to determine the psychosocial interventions targets - A. V. Vasileva; T. A. Karavaeva; D. S. Radionov; A. V. Yakovlev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
A cohort cross-sectional study of the attitude of the population to vaccination against coronavirus infection COVID-19 was carried out using a specially designed questionnaire for mass filling, located on Internet resources 2 months after the start of mass vaccination in Russia. A total of 4172 people were examined at the age from 18 to 81 years. Among the respondents, there were different tendencies in relation to vaccination. Of the total sample, 35.7% of respondents consider vaccination useful, 32.2%—doubt its effectiveness, 8.7%—consider vaccination unnecessary, 12.2%—dangerous, indifference to vaccination was formed in 5.9% of respondents. They indicated that they do not plan to be vaccinated, 30.8%, postpones their decision until more remote data on the results and effectiveness of vaccination are obtained—34.7%, were vaccinated at the time of the study—12.2%. Young people are less focused on vaccination than middle-aged and older people. Among the factors that are associated with the attitude towards vaccination are age, gender, education, fear of possible complications, fear of contracting a coronavirus infection, concern for the health of their loved ones, anxiety about the current situation with coronavirus in general. The reports of scientists, doctors and experts in this field are essential for shaping attitudes towards vaccination. The study results should be considered as the targets for vaccination behavior improvement psychosocial interventions for different social and age population groups